Artificially disordered birefringent optical fibers - Herath, S.; Puente, N. P.; Chaikina, E. I.; Yamilov, A. (2012)
We develop and experimentally verify a theory of evolution of polarization in artificially-disordered multi-mode optical fibers. Starting with a microscopic model of photo-induced index change, we obtain the first and second order statistics of the dielectric tensor in a Ge-doped fiber, where a volume disorder is intentionally inscribed via UV radiation transmitted through a diffuser. A hybrid coupled-power & coupled-mode theory is developed to describe the transient process of de-polarization of light launched into such a fiber. After certain characteristic distance, the power is predicted to be equally distributed over all co-propagating modes of the fiber regardless of their polarization. Polarization-resolved experiments, confirm the predicted evolution of the state of polarization. Complete mode mixing in a segment of fiber as short as ∼ 10cm after 3.6dB insertion loss is experimentally observed. Equal excitation of all modes in such a multi-mode fiber creates the conditions to maximize the information capacity of the system under e.g. multiple-input-multiple-output (MIMO) transmission setup.